ETIKA DISKUSI DALAM PERSPEKTIF AL-QUR’AN - Zulfikar, Eko (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
In the discussion forum, of course, there is the variability of arguments from various parties in order to get the objectives to be achieved. There is a discussion that ends sweetly with a good solution, there is also a discussion that ends with a dispute that causes hostility. Therefore, in a discussion, a code of ethics is needed for a conducive and constructive atmosphere of discussion. This paper will introduce how the ethics of discussion summarized in the Koran. By using the thematic method, it was concluded that there were at least seven ethical discussions in the perspective of the Qur'an, namely; sincere and true intentions, pay attention and listen well to the other person, armed with knowledge and strong-accurate argumentation, using clear-straightforward and gentle rhetoric, being fair and objective, being cooperative and being ready to return to the truth, and avoiding a nagging attitude - do not want to budge and want to win alone. With this ethic, it is expected that the hostility raised in the discussion can be avoided and the purpose of the discussion created is to create an atmosphere of intimacy and mutual understanding. Keyword: Discussion, Ethics, Qur'an, Thematic Interpretations